Coalescence of multiple droplets induced by a constant DC electric field. - Liwei Sun; Jian Wang; Yanhui Chen (PLoS ONE, 2024)
In this work, the electro-coalescence process of three nanodroplets under a constant DC electric field is investigated via molecular dynamics simulations (MD), aiming to explore the electric manipulation of multiple droplets coalescence on the molecular level. The symmetrical and asymmetrical dynamic evolutions of electrocoalescence process can be observed. Our MD simulations show that there are two types of critical electric fields to induce the special dynamics. The chain configuration can be formed, when one of the critical electric field is exceeded, referred to as Ecc. On the other hand, there is another critical electric field to change the coalescence pattern from complete coalescence to partial coalescence, the so-called Ecn. Finally, we find that the use of the pulsed DC electric field can overcome the drawbacks of the constant DC electric field in the crude oil industry, and the mechanisms behind the suppressed effect of the water chain or non-coalescence are further revealed.